Efficacy of Homeopathic Medicines in Management of Irritable Bowel Syndrome (Advancements in Homeopathic Research, 2024)
This 21st century act as a double –edged sword on the  modern civilization. In this era, a group of people are  in rat race competition. This brings mental stress and  strain which causes developmental of gastrointestinal  disease. Irritable bowel syndrome is multifactorial disorder  of GIT tract causing disturbances in gastric motility,  resulting in abdominal pain and altered bowel  habits. A changing lifestyle and modernization  imply a change in eating habits, decreased sleep and  increase in stressful competitive atmosphere. These  factors contribute to large number of psychosomatic  disorders. IBS is a common cause of referral and  accounts for frequent absenteeism from work and  impaired quality of life.
Keywords: Irritable bowel syndrome; Management; Homoeopathy